Design of primer Ipomoea batatas chloroplast gene matK - S. Syamsurizal; Ardi Ardi; Des M; Resti Fevria; Yusni Atifah; Elsa Badriyya; Afifatul Achyar (Genetikawan Muda Indonesia, 2021)
Sweet potato varieties (Ipomoea batatas) Pucuk Hitam Panyalaian and Madu Pucuk Hitam Panyalaian have the potential to be a superior commodity in West Sumatra, but the information of genetic diversity is very limited. Data on the diversity of sweet potato germplasm is beneficial in the selection of plants to obtain superior cultivars in plant breeding. Aim: The aim of the study was to find specific primers for the study of sweet potato genetic markers using Ipomoea batatas chloroplast genes matK. Methods: DNA extraction from sweet potato young leaves; designing forward and reverse primers Ipomoea batatas chloroplast genes matK; PCR; sequencing; bioinformatics analysis and species identification by comparing the NCBI database. Results: Plant DNA barcoding PCR using designed primers matK were successfully resulting single DNA band in different amplicon size in some samples. This indicating that the designed primers used were able to distinguish variation in one species.